Time-Resolved Calibration of Photon Detection Efficiency and Afterpulse Probability in 100 MHz Gated InGaAs/InP Single-Photon Avalanche Diodes - Zeyun Wang; Yiping Zhang; Hanqin Gu; Chao Han; Liang Yin; Yan Liang (Photonics, 2025)
InGaAs/InP single-photon avalanche diodes (SPADs) are widely used in applications such as quantum information, deep-space communication, and LiDAR. However, the existence of afterpulsing effects leads to inaccuracies in the calibration of their performance, particularly in terms of photon detection efficiency (PDE). In this paper, we employ the capacitance-balancing method to achieve a 100 MHz gated InGaAs/InP SPAD and propose a time-correlated calibration method to measure its performance. The distribution of the afterpulse counts over time is predicted, enabling a valid distinction between photogenerated counts and error counts. A PDE higher than ~30% is reached with an afterpulse probability of ~15%, while the repetition frequency of the incident laser (flaser) changes from 1 MHz to 50 MHz. A comparison of the existing methodologies for calculating PDE reveals that PDE increases with flaser. This increase is particularly pronounced when the PDE is high. However, under the time-correlated calibration scheme employed, the PDE remains almost constant, thereby validating the reliability of the results.